2019
DOI: 10.1111/ajag.12630
|View full text |Cite
|
Sign up to set email alerts
|

Dissonance on perceptions of end‐of‐life needs between health‐care providers and members of the public: Quantitative cross‐sectional surveys

Abstract: Objective To investigate views, determinants and barriers to end‐of‐life discussions for doctors, nurses and members of the public (MoP) and their acceptability of risk prediction tools. Methods Concurrent surveys of 360 doctors and nurses and 497 MoP. Results Sixty per cent of clinicians reported high confidence in initiating end‐of‐life discussions, and 55.8% regularly engaged in them. Barriers to end‐of‐life communication reported by clinicians were uncertainty on the likely time to death (44.7%) and family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…Another recent study revealed a discrepancy between patient preferences for EOL care, including lifesustaining treatment (LST), and physician recommendations on EOL care [10,11], but it is unclear whether differences also exist between patients and nurses or care staff with an essential role in providing EOL care.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study revealed a discrepancy between patient preferences for EOL care, including lifesustaining treatment (LST), and physician recommendations on EOL care [10,11], but it is unclear whether differences also exist between patients and nurses or care staff with an essential role in providing EOL care.…”
Section: Introductionmentioning
confidence: 99%
“…The clinician’s ethical duty to break bad news and allow time for patients and families to come to terms with the inevitable needs to be balanced with the patient readiness for hearing poor prognosis [ 28 ]. The preference to receive full prognostic disclosure varies across cultures and settings and may be changing with time, as suggested by the findings of two population surveys in 2015 in Brazil [ 29 ] and Australia [ 30 ] reporting that a majority of older members of the public wanted to know if they had less than a year to live. By contrast, a 2003 survey of older community dwellers with life-limiting illness and their caregivers in the USA [ 31 ] and a 2008 Canadian survey of inpatients with advanced chronic lung disease [ 32 ] reported that many did not want prognostic disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, overcoming barriers is important in achieving widespread use of ACP. Among reported barriers are uncertainty, lack of comfort and lack of knowledge among health care personnel in doing ACP [13,28,[36][37][38]. Implementation of ACP thus warrants proper education, training and follow-up of health care personnel and leaders.…”
Section: Public Attitudes On Acp Participationmentioning
confidence: 99%
“…Internationally, there are studies on older people's attitudes towards ACP [11,12] and on the public's attitudes [13][14][15][16]. They indicate that while most people have thought about end-of-life care and decision-making [14] there is a wish for information about prognosis, diagnosis and available treatments when facing life-limiting illness [13,15]. Furthermore, most seem willing to participate in conversations on end-of-life care [11,12,16].…”
Section: Introductionmentioning
confidence: 99%